A novel UBE3A sequence variant identified in eight related individuals with neurodevelopmental delay, results in a phenotype which does not match the clinical criteria of Angelman syndrome. Issue 11 (5th September 2020) - Geerts‐Haages, Amber; Bossuyt, Stijn N. V.; den Besten, Inge; Bruggenwirth, Hennie; van der Burgt, Ineke; Yntema, Helger G.; Punt, A. Mattijs; Brooks, Alice; Elgersma, Ype; Distel, Ben; Valstar, Marlies
Abstract: Background: Loss of functional UBE3A, an E3 protein ubiquitin ligase, causes Angelman syndrome (AS), a neurodevelopmental disorder characterized by severe developmental delay, speech impairment, epilepsy, movement or balance disorder, and a characteristic behavioral pattern. We identified a novel UBE3A sequence variant in a large family with eight affected individuals, who did not meet the clinical AS criteria. Methods: Detailed clinical examination and genetic analysis was performed to establish the phenotypic diversity and the genetic cause. The function of the mutant UBE3A protein was assessed with respect to its subcellular localization, stability, and E3 ubiquitin ligase activity. Results: All eight affected individuals showed the presence of a novel maternally inherited UBE3A sequence variant (NM_130838.4(UBE3A):c.1018‐1020del, p.(Asn340del), which is in line with a genetic AS diagnosis. Although they presented with moderate to severe intellectual disability, the phenotype did not match the clinical criteria for AS. In line with this, functional analysis of the UBE3A p.Asn340del mutant protein revealed no major deficits in UBE3A protein localization, stability, or E3 ubiquitin ligase activity. Conclusion: The p.(Asn340del) mutant protein behaves distinctly different from previously described AS‐linked missense mutations in UBE3A, and causes a phenotype that is markedly different from AS. This study further extends the range of phenotypes that are associated with UBE3A loss, duplication, or mutation. Abstract : We report on the clinical phenotype and functional characterization of a novel maternally‐inherited UBE3A sequence variant, p.Asn340del, that was identified in a large family with eight affected individuals. We show that the p.Asn340del mutant protein behaves distinctly different from previously described Angelman syndrome (AS)‐linked missense mutations in UBE3A, and causes a phenotype that does not match the clinical criteria for AS. This study further extends the range of phenotypes that are associated with UBE3A loss, duplication or mutation.